A world catalogue of Phragmataecia (Lepidoptera: Cossidae), with a new species from Kazakhstan and Kyrgyzstan - Yakovlev, Roman V. (Zootaxa, 2016)
Phragmataecia valikhanovi Yakovlev & Witt sp. nov. is described from Kazakhstan and Kyrgyzstan. The Catalogue of the Genus Phragmataecia Newman, 1850 is provided.